Analysis of handwriting patterns of Dyslexic Children vis-à-vis the nondyslexics using Hamming Distance (International Journal of Engineering and Computer Science, 2017)
Learning disabilities can affect a person's ability to speak, listen, read, write, spell, reason, recall, organize information, and do mathematics. Researcher has tried to study what could be the percentage of children having writing difficulties among all types of Learning Disability. In this paper, the researcher has focused particularly on Dysgraphia. The survey conducted with a group of Learning Disabled children and the researcher wanted each of them to identify certain words. This study is to investigate in which pattern of the text Dysgraphia child finds difficulty to understand and by how much error factor a Dysgraphia child is distinctly identifiable from nonDysgraphia one.